2019
DOI: 10.1515/ijcre-2018-0265
|View full text |Cite
|
Sign up to set email alerts
|

A Micromixer with Two-Layer Crossing Microchannels Based on PMMA Bonding Process

Abstract: A micromixer with two-layer crossing microchannels based on PMMA bonding process was proposed. The micromixer consists of two-layer crossing microchannels and periodic mixing chambers. The numerical simulation and parameters optimization of the micromixer were carried out in a Reynolds number range of 0.5–100 using CFD software, and the prototype of micromixer was manufactured by PMMA bonding process under certain temperature and pressure condition. The mixing performance of the micromixer was tested and verif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The proposed micromixer offers an improvement in mixing performances over micromixers of the same category reported previously. Wang et al 24 have suggested a new three-dimensional two-layer micromixer, which is manufactured by the PMMA bonding process. Their numerical and experimental results demonstrate that the proposed micromixer exhibits a good mixing efficiency for a wide range of Reynolds numbers from 0.5 to 100, such that a mixing index of 91.5% is obtained at Re = 5, while at Re = 100, the mixing efficiency reaches 98.6%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed micromixer offers an improvement in mixing performances over micromixers of the same category reported previously. Wang et al 24 have suggested a new three-dimensional two-layer micromixer, which is manufactured by the PMMA bonding process. Their numerical and experimental results demonstrate that the proposed micromixer exhibits a good mixing efficiency for a wide range of Reynolds numbers from 0.5 to 100, such that a mixing index of 91.5% is obtained at Re = 5, while at Re = 100, the mixing efficiency reaches 98.6%.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed micromixer offers an improvement in mixing performances over micromixers of the same category reported previously. Wang et al . have suggested a new three-dimensional two-layer micromixer, which is manufactured by the PMMA bonding process.…”
Section: Introductionmentioning
confidence: 99%